Effect of molecular weight and pH on the self-assembly microstructural and emulsification of amphiphilic sodium alginate colloid particles. (June 2020) - Fang, Xiuqin; Zhao, Xinyu; Yu, Gaobo; Zhang, Lei; Feng, Yuhong; Zhou, Yang; Liu, Yuanyuan; Li, Jiacheng
Abstract: Biopolymer-based Pickering emulsions have attracted increasing interest in research areas including food, pharmaceutics and drug delivery. However, understanding of self-assembly behavior from the dedicate structure of stabilizers has not been well explored yet. In this work, we proposed to investigate how molecular weight affect the self-assembly behavior and to explore the potential of biopolymer colloidal particle-stabilized Pickering emulsion for controlling release of hydrophobic drugs. Amphiphilic sodium alginate derivatives (Ugi-Alg) with three molecular weights (685 kDa, 307 kDa and 48 kDa) were successfully incorporated with a hydrophobic group. Based on the characterizations of morphology and rheology behavior, the high-molecular-weight derivatives (H-Ugi-Alg) can form a compact micelle structure in aqueous solution. Emulsions stabilized by H-Ugi-Alg exhibited a higher stability and stronger viscoelasticity than those using Ugi-Alg with a lower molecular weight. In addition to the entangled polymer chains caused by higher molecular weight and hydrophobic association, the partially protonated carboxyl groups reduced electrostatic repulsion at pH = 4.2 also facilitate the formation of compact micelle structure. Approximately 78.6% of the encapsulated curcumin released from the emulsion stabilized by H-Ugi-Alg, which exhibits a similar release efficiency compared with the nanoparticle-stabilized Pickering emulsions. Graphical abstract: Image 1 Highlights: The molecular weight and pH of Ugi-Alg and pH play important roles in the construction of micelles and the emulsion properties. The micelles formed by H-Ugi-Alg at pH = 4.2 in aqueous solution adopted spherical structure with small particle size. Emulsions stabilized by H-Ugi-Alg exhibited great stability, strong viscoelasticity and small droplet size. H-Ugi-Alg micelles were adsorbed at the oil-water interface to form a protective film, to prevent droplet migration. Emulsions stabilized by Ugi-Alg were proved to have the potential of controlling release of hydrophobic drugs.